PENGARUH KETELADANAN GURU TERHADAP PEMBENTUKAN KARAKTER RELIGIUS SISWA DI MTSN 1 KOLAKA UTARA - Ahmad Syaidul Angkasa; Wakib Kurniawan (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2026)
This study aims to analyze the effect of teacher exemplarity on the formation of students’ religious character at MTsN 1 Kolaka Utara. This research employed a quantitative approach with an ex post facto design. The population consisted of all students at MTsN 1 Kolaka Utara, and the sample was determined using proportional random sampling. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis techniques included descriptive analysis and simple linear regression. The results showed that teacher exemplarity was in the good category with a mean score of 3.87, while students’ religious character was also in the good category with a mean score of 3.92. Hypothesis testing revealed that teacher exemplarity had a positive and significant effect on students’ religious character, with a significance value of 0.000 (< 0.05) and a coefficient of determination of 0.42. This indicates that teacher exemplarity contributes 42% to the formation of students’ religious character. Therefore, teacher exemplarity plays a crucial role in the internalization of religious values in the school environment.